(3efXhQ JcfhdhLjs - (3eRgQ TYHGf(B, (3GdYGfjs ((3YeGf(B:s (3OGQ hGFd ddfTQ(B,s, 2009)
(3fXe eYdheGJ GdCYeGd,fXe GdeYdheGJ GdESJQGJjLjI,JcfhdhLjG GdeYdheGJ,GdeYOGJ GdeGOjI dJcfhdhLjG GdeYdheGJ,GdeYOGJ GdHQeLjI dJcfhdhLjG GdeYdheGJ,bhGYO GdHjGfGJ heNGRf GdHjGfGJ,GdTHcGJ hGdEJUGdGJ,GdEJUGdGJ GddGSdcjIs
(3HHdjhZQGajG(B:(3U(B.263-271s
Keywords: (3GdEOGQIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s